Hamburguesa de boquichico (Prochilodus nigricans) con micropartículas conteniendo aceite de sacha inchi (Plukenetia volubilis L.) - Huamaní Mendoza, Patricia Lizbeth (2022)
Hamburgers are the most consumed processed meat products worldwide, however, it is well known that they have a high content of saturated fats, due to this different studies have opted for the reformulation of this product, using healthier meats such as fish and modifying its lipid profile. The objective of this study is to prepare boquichico (Prochilodus nigricans) fillet hamburger with substitution of pork fat with different amounts of microencapsulated sacha inchi oil by spray drying and to evaluate the pulp and cooking yields, the nutritional value, and the sensory acceptability of the hamburger. In this study, several types of boquichico fillet hamburgers r were produced to replace saturated fat with polyunsaturated fat with different concentrations of microparticles containing sacha inchi oil T1 (C); T2 (free oil); T3 (15% of substitution); T4 (20% of substitution); T4 (25% of substitution); T6 (30% of substitution). The hamburgers were characterized physicochemically, lipid profile and acceptance tests. Burgers with and without partial fat substitution showed on average about 18% protein and total lipid. There was a statistically significant difference between the hamburgers with substitution of 15%, 20%, 25% and 30%, the general acceptability scores showed that the hamburger containing 15% of microencapsulated oil had a positive response. The pulp yield reached 35.50%, the addition of microencapsulated oil produced hardness around 98% for substitutions of 15% to 25%. The results show that the modification of the formulation of the hamburgers with substitution of pork fat is feasible and it can be seen as an alternative to improve the nutritional composition without affecting the physical, chemical and sensory properties of the resulting hamburgers.